The Academic Book of the Future. - Lyons, Rebecca E. (Palgrave Macmillan UK, 2016)
This book is open access under a CC-BY licence. Part of the AHRC/British Library Academic Book of the Future Project, this book interrogates current and emerging contexts of academic books from the perspectives of thirteen expert voices from the connected communities of publishing, academia, libraries, and bookselling.